Pengembangan lembar kerja peserta didik berbasis pendekatan saintifik pada pembelajaran IPA kelas V DI SD Negeri Tegalpanggung Yogyakarta - Tessa, Namira Chyka; Utaminingsih, Retno (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to: 1) develop LKPD based on a scientific approach in science learning in grade V of elementary school; 2) to determine the feasibility of LKPD based on a scientific approach in science learning in grade V of elementary school by material experts, media experts, and class teachers; 3) to determine students' responses to LKPD based on a scientific approach in science learning in grade V of elementary school. This study is a Research and Development (R&D) study with the ADDIE development model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques use unstructured interview techniques, observation, and questionnaires in the form of a multilevel/likert scale. Data analysis techniques use qualitative data analysis and quantitative data analysis. The feasibility of the media is obtained from the validation results carried out by material experts, media experts, and class teachers using instruments in the form of validation questionnaires, and students using instruments in the form of response questionnaires. The results of the study indicate that 1) the study produced a LKPD product based on a scientific approach in science learning for grade V elementary schools with a focus on the material on the